Investigating the Impact of Airport Relocation on the Transport Network in Special Region of Yogyakarta, Indonesia - Andrean Gita Fitrada (Journal of the Civil Engineering Forum, 2019)
Adi Sutjipto International Airport is the airport currently operated in Special Region of Yogyakarta (SRY), located near the city centre area. SRY needs to construct a new airport due to the increase in air passengers. The proposed airport, named New Yogyakarta International Airport (NYIA) is located in the undeveloped area, away from the city centre. This study is aimed to investigate the impact of airport relocation to the road network and to assess several developments of transportation infrastructures to the new airport.  The analysis was conducted by developing a transport network model using PTV Visum. The secondary data collected from the local government to develop the transport network model, including the development of origin-destination matrices and forecasting purpose.  The scenarios of road infrastructures development and new rail service to the airport in 2025 are then modelled. The results showed that the road infrastructure developed can reduce the number of congested main roads from 9.47% into 5.94%. Rail service to the airport is effective to decrease the traffic congestion at two NYIA roads access and able to increase their average speed from 49.45 and 44.29 km/h into 66.45 and 62.66 km/h.